PENGUKURAN LAJU DOSIS PAPARAN RADIASI HAMBUR PADA RUANG COMPUTER TOMOGRAPHY (CT) SCAN DI RUMAH SAKIT BHAYANGKARA MAKASSAR - Astuti, Astuti; Sahara, Sahara; Zelviani, Sri (JFT: Jurnal Fisika dan Terapannya, 2018)
This research aims to determine the effect of exposure to radiation dose on the distance from the radiation source, determine radiation dose exposure with variations in exposure factors (voltage), and to determine the radiation exposure received by workers / operators in the CT-Scan room at Bhayangkara Hospital Makassar and using a sensitive Surveymeter with variations in the exposure factor (voltage) of 100 kV, 120 kV, and 135 kV and a variation of the distance from the radiation source of 0 m, 1 m, 2 m. The results showed that the highest dose was on the front side with a voltage of 135 kV at a distance of 0 m, namely 1.5 nSv / h. While the lowest dose is on the left side with a voltage of 100 kV at a distance of 2 m, namely 0.6 nSv / h. Radiation exposure received by workers / operators in the CT-Scan room at Bhayangkara Hospital Makassar at a voltage of 135 kV, a distance of 1 m from the radiation source, namely 1.5 nSv / h. This is in accordance with the provisions of BAPATEN, namely the value of the dose received does not exceed 50 mSv in (one) year.